Towards a better diagnosis and treatment of dementia: Identifying common and distinct neuropathological mechanisms in Alzheimer's and vascular dementia - Vollhardt, Alisa; Frölich, Lutz; Stockbauer, Anna Christina; Danek, Adrian; Schmitz, Christoph; Wahl, Anna-Sophia (Neurobiology of disease, 2025)
Alzheimer's disease (AD) and vascular dementia (VaD) together contribute to almost 90 % of all dementia cases leading to major health challenges of our time with a substantial global socioeconomic burden. While in AD, the improved understanding of Amyloid beta (Aß) mismetabolism and tau hyperphosphorylation as pathophysiological hallmarks has led to significant clinical breakthroughs, similar advances in VaD are lacking. After comparing the clinical presentation, including risk factors, disease patterns, course of diseases and further diagnostic parameters for both forms of dementia, we highlight the importance of shared pathomechanisms found in AD and VaD: Endothelial damage, blood brain barrier (BBB) breakdown and hypoperfusion inducing oxidative stress and inflammation and thus trophic uncoupling in the neurovascular unit. A dysfunctional endothelium and BBB lead to the accumulation of neurotoxic molecules and Aß through impaired clearance, which in turn leads to neurodegeneration. In this context we discuss possible neuropathological parameters, which might serve as biomarkers and thus improve diagnostic accuracy or reveal targets for novel therapeutic strategies for both forms of dementia.